How to conduct surveys : a step-by-step guide - Fink, Arlene (Los Angeles [i.e. Thousand Oaks, Calif.] : SAGE Publications, 2013)
"The Fifth Edition of the best-selling How to Conduct Surveys guides readers through the process of developing their own rigorous surveys and evaluating the credibility of surveys created by others. Offering practical, step-by-step advice and written in the same clear and accessible style as her other works, author Arlene Fink centers her guidance on choosing the appropriate type of survey, writing survey questions and responses, formatting the survey, deciding on the characteristics and numbers of respondents to include, determining the frequency of surveying respondents, and analyzing and reporting the results. The Fifth Edition pays particular attention to the internet and online surveys, considering best practices and techniques for developing a thorough and effective survey."--Publisher.
Conducting surveys : everyone is doing it -- The survey form : questions, scales, and appearance -- Getting it together : some practical concerns -- Sampling -- Survey design : environmental control -- Analyzing and organizing data from surveys -- Presenting the survey results.
Includes bibliographical references and index.
Keywords: Social surveys; Educational surveys; Educational surveys; Social surveys; metodik; Data Collection; Surveys and Questionnaires; Data Collection